Analisis Pengembangan Organisasi Pelayanan Publik di Rumah Sakit Umum Daerah dengan Model Weisbord - Asmara, Denie Candra; Madjir, Sulbahri; Basyith, Abdul (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Regional General Hospital is one of the public service organizations with the obligation to provide health services that are quality, safe, effective, do not discriminate, and prioritize patients. The background for conducting this research is that customer satisfaction at Semende Darat Laut Hospital has not reached the standard, which means there are several causes, including lack of empathy, lack of information, lack of response, and long service time. This research was conducted to determine and analyze the inhibiting factors in health services through diagnosis and intervention in developing hospital organizations. The research method is a survey that distributes questionnaires to all 25 civil servant staff at Semende Darat Laut Regional Hospital for analysis using the